2016
DOI: 10.1177/1077546316642054
|View full text |Cite
|
Sign up to set email alerts
|

The influence of localized randomness on regular grazing bifurcations with applications to impacting dynamics

Abstract: This paper concerns stochastic perturbations of piecewise-smooth ODE systems relevant for vibro-impacting dynamics, where impact events constitute the primary source of randomness. Such systems are characterized by the existence of switching manifolds that divide the phase space into regions where the system is smooth. The initiation of impacts is captured by a grazing bifurcation, at which a periodic orbit describing motion without impacts develops a tangential intersection with a switching manifold. Oscillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…For β = π/6 we numerically detect a different type of critical point for the 2:1 period-2 solutions, namely, grazing bifurcations as indicated by the vertical lines at d = G 1 and d = G 2 in Figure 5 (j)-(l), at which Żj = 0 and Z j = d/2 [42,44,47]. Figure 8 zooms in on the bifurcation branches near these values.…”
Section: The Grazing Transition and Bistabilitymentioning
confidence: 89%
See 1 more Smart Citation
“…For β = π/6 we numerically detect a different type of critical point for the 2:1 period-2 solutions, namely, grazing bifurcations as indicated by the vertical lines at d = G 1 and d = G 2 in Figure 5 (j)-(l), at which Żj = 0 and Z j = d/2 [42,44,47]. Figure 8 zooms in on the bifurcation branches near these values.…”
Section: The Grazing Transition and Bistabilitymentioning
confidence: 89%
“…Vibro-impact systems have rich phenomenological behaviors, manifesting various nonlinear phenomena like bifurcations, grazing and chaos. These effects have been studied in deterministic and stochastic vibroimpact systems, as in [38][39][40][41][42][43][44][45][46][47] among others. The models of vibro-impact systems include piecewise linear stiffness [48,49] as well as rigid barriers and instantaneous impacts leading to a velocity jump for inelastic impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Shen [12][13] considered an impact oscillator, suppressed the jumping phenomenon at the grazing bifurcation point based on the special dynamic characteristics of the continuous transition at the degenerated grazing bifurcation point. Simpson [14] considered a kind of impact oscillators with random excitation, and gave the dynamic behavior induced by grazing under different random excitation. Simpson [15] considered a class of single-degree-of-degree impact oscillators, which revealed that some truncated terms neglected in the Nordmark mapping had important effects on the dynamics characteristics of the real primary system.…”
Section: Introductionmentioning
confidence: 99%
“…Shen [12][13] considered an impact oscillator, suppressed the jumping phenomenon at the grazing bifurcation point based on the special dynamic characteristics of the continuous transition at the degenerated grazing bifurcation point. Simpson [14] considered a kind of impact oscillators with random excitation, and gave the dynamic behavior induced by grazing under different random excitation. Simpson [15] considered a class of single-degree-of-degree impact oscillators, which revealed that some truncated terms neglected in the Nordmark mapping had important effects on the dynamics characteristics of the real primary system.…”
Section: Introductionmentioning
confidence: 99%